ANALISIS VO2 MAX TIM FUTSAL SMA NEGERI 22 MAKASSAR - Benny Badaru; sufitriyono sufitriyono (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2021)
This research generally aims to give an idea of the extent of the VO2Max ability of the futsal team at SMA Negeri 22 Makassar. The subjects of this study were 20 students from the SMA Negeri 22 Makassar team, this sample was also called the "saturated sample". The sampling technique used in this study uses a total sampling technique. Data collection techniques in this study are using observation sheets and bleep test forms. Research instruments in the study for data collection in this study using the Bleep Test. Data analysis techniques in the study used descriptive statistical analysis. The results of this study indicate that the ability of the VO2Max level of the futsal team at the 22nd High School Makassar Makassar is in the medium category with a mean value (42.375) with detailed data that is in the excellent criteria of 0 students (0%), on good criteria a number of 10 students ( 50%), students on the medium criteria were 10 people (50%) and students who were included in the criteria were poor and the criteria were very few at 0 students (0%). The conclusion of this study is the VO2Max level of the Futsal Team at SMA Negeri 22 Makassar is in the medium category.